VD_FINDINFO Décision / 2013 / 28 vom 8. Januar 2013 - VD Tribunal cantonal (2013)
RADIATION DU RÔLE, LANGUE DE LA PROCÉDURE, CONCLUSIONS, MOTIF DU RECOURS | 61 let. b LPGA, 26 al. 1 LPA-VD, 27 al. 4 LPA-VD, 27 al. 5 LPA-VD, 79 al. 1 LPA-VD, 94 al. 1 let. c LPA-VD, 99 LPA-VD